Association between weight status and motor competence in schoolchildren from Chilean Patagonia - Cumilef-Bustamante, Pablo; Millalonco, Oscar; Díaz Alvarado, Mauricio Andrés; Rivera-Gutierrez, Catalina; Henriquez-Alvear, Luis; Carcamo-Oyarzu, Jaime; Delgado-Floody, Pedro (My University, 2024)
Background: the prevalence of overweight and obesity in the child population is a global public health problem, with measures such as the promotion of physical activity being necessary. One of the recognized factors for this is the development of motor competence, due to its dynamic interaction with physical activity, so it is necessary to understand its relationship with weight status. Objective: the aims of this study are to determine whether there are differences in the levels of motor competence of schoolchildren in Chilean Patagonia according to their nutritional status, as well as to determine the association between body mass index (BMI) and the levels of motor competence in these schoolchildren. Material and methods: we evaluated 295 boys and girls in 5 th and 6 th grade of primary school, from educational centres in Coyhaique and Punta Arenas. We used the MOBAK 5-6 test to assess their motor competence. Results: schoolchildren with normal weight status presented higher values of motor competence in self-movement (M = 3.1; SD = 1.84) compared to overweight (M = 2.7; SD = 1.68) and obese schoolchildren (M = 1.7; SD = 1.57), presenting significant differences between all groups (p < 0.001). In object control, no differences were found between the groups. In addition, there was an inverse association of object control with gender (3: 3: 1.49; p < 0.001) and BMI (beta:-0.05; p = 0.026), while self-movement had an inverse association with BMI (beta:-0.11; 95 % CI:-0.15-0.07; p < 0.001). Conclusion: weight status and motor competence are associated. Schoolchildren with higher BMI values tend to perform lower in self-movement. These results underline the importance of addressing motor competence in efforts to combat overweight and obesity in children.
Keywords: motor skills; motor development; weight status; physical activity; physical literacy; students